Learning while setting precedents - Ying Chen; Hülya Eraslan (Osaka University, Institute of Social and Economic Research (ISER), 2020)
A decision maker makes a ruling on a random case in each period. She is uncertain about the correct ruling until conducting a costly investigation. A ruling establishes a precedent, which cannot be violated under binding precedent. We compare the information acquisition incentives, the evolution of standards and the social welfare under nonbinding and binding precedents. Compared to non-binding precedent, under binding precedent, information acquisition incentives are stronger in earlier periods, but become weaker as more precedents are established. Although erroneous rulings may be perpetuated under binding precedent, welfare can be higher because of the more intensive investigation early on.
Keywords: D02; D23; D83; K4; 330; precedent; binding precedent; information acquisition; transparency